COMPARATIVE ANALYSIS OF ZAKAT DISTRIBUTION PROGRAM IN RIAU PROVINCE IN INDONESIA AND SELANGOR STATE IN MALAYSIA IN REDUCING POVERTY: A DYNAMIC ANALYSIS MODEL (International Journal of Islamic Business, 2020)
This study is a comparative study between Riau Province in Indonesia and Selangor State in Malaysia with the aim of assessing differences in the zakat distribution program in reducing poverty in both regions, using the Tawhidi String Relationship (TSR) theory with a circular causation approach and a dynamic analysis model. The results of the study found that there were differences in the management of zakat in the two regions, differences in the effect of reducing poverty, differences in the amount of zakat collected and differences in the distribution of zakat funds. Research recommendation is Riau Province should unite the management of zakat in one institution to concentrated zakat funds and the distribution of zakat has a stronger multiplier effect in reducing poverty.